Managed Trade : What Could be Possible Spillover Effects of a Potential Trade Agreement Between the U.S. and China? - Cerutti, Eugenio (IMF Working Papers; Working Paper, 2019)
The trade discussions between the U.S. and China are on-going. Not much is known about the shape and nature of a potential agreement, but it seems possible that it would include elements of managed trade. This paper attempts to examine the direct, first-round spillover effects for the rest of the world from managed trade using three approaches. The results suggest that, in the absence of a meaningful boost in China's domestic demand and imports, bilateral purchase commitments are likely to generate substantial trade diversion effects for other countries. For example, the European Union, Japan, and Korea are likely to have significant export diversion in a potential deal that includes substantial purchases of U.S. vehicles, machinery, and electronics by China. At the same time, a deal that puts greater emphasis on commodities would put small commodity exporters at a risk. This points to the advantages of a comprehensive agreement that supports the international system and avoids managed bilateral trade arrangements.